El bastón, la consonante y la mentalidad técnica moderna (2021)
This paper presents technique and technology as phenomena connected with the human language and the modern vision of the world. With alphabetic language and the invention of the consonant, the human being passes from the practical knowedge of the name to the abstract knowledge of the concept. The illiterate distinguishes concrete things by their names, but the literate knows them through the abstract categories they belong to. In modern times, human beings split the quantitative or objective aspects from the qualitative or subjective aspects of reality and describe it by formulas, reducing it to a repository of mathematically quantifiable energy to extract, measure, and apply it to transform the environment and themselves. The modern technical mentality in its most extreme expression represents not only a dangerous situation but also an opportunity for integrally human progress. Finally, it is a matter of thinking about the synergy between the technical object, its environment, and the human beings, and also about the synergy between all techniques.